Development of an evaluation method for planning of urgent protection strategies in a nuclear emergency using a level 3 probabilistic risk assessment. Issue 3 (4th March 2021) - Kimura, Masanori; Oguri, Tomomi; Ishikawa, Jun; Munakata, Masahiro
ABSTRACT: The authors developed an evaluation method for planning urgent protection strategies in a nuclear emergency by using a Level 3 Probabilistic Risk Assessment (PRA) code, OSCAAR. For a given accident scenario, the OSCAAR can calculate received doses in the early phase of a nuclear accident and the dose reduction effect of implementing urgent protective actions such as evacuation, sheltering, and iodine thyroid blocking. The authors considered the combination of these urgent protective actions within a precautionary action zone (PAZ) and an urgent protective action planning zone (UPZ) for an accident scenario and then calculated received doses after implementing these protective actions using the OSCAAR. After that, the authors performed sensitivity analysis for protective action models of the OSCAAR and then optimized the protection strategy by reducing doses to below generic criteria of the International Atomic Energy Agency (IAEA). Consequently, the effective urgent protection strategy for the accident scenario could be designed, such as precautionary evacuation within the PAZ, and the combination of evacuation after sheltering, sheltering in concrete building, or in normal housing and thyroid blocking within the UPZ. The developed evaluation method will be very useful in developing effective urgent protection strategies for an accident scenario.